The Green state : environmental security and biodiversity in Guyana - Granger, David A. (Ministry of the Presidency GeorgetownGY, 2016)
Presents the addresses by HE David A, Granger, President of the Cooperative Republic of Guyana including that at the signing of the Paris Agreement.